BLOOD DOPING AND RISKS - Goran Vasić; Dragoslav Jakonić; Slavko Molnar; Branka Protić-Gava (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2015)
Doping is the way in which athletes misuse of chemicals and other types of medical interventions (eg, blood replacement), try to get ahead in the results of other athletes or their performance at the expense of their own health. The aim of this work is the analysis of blood doping and the display of negative consequences that this way of increasing capabilities brings. Method: The methodological work is done descriptively. Results: Even in 1972 at the Stockholm Institute for gymnastics and sport, first Dr. Bjorn Ekblom started having blood doping. Taken from the blood, athletes through centifuge separating red blood cells from blood plasma, which is after a month of storage in the fridge, every athlete back into the bloodstream. Tests aerobic capacity thereafter showed that the concerned athletes can run longer on average for 25% of the treadmill than before. Discussion: Blood doping carries with it serious risks, excessive amount of red cells "thickens the blood," increased hematocrit, which reduces the heart's ability to pump blood to the periphery. All this makes it difficult for blood to flow through blood vessels, and there is a great danger that comes to a halt in the circulation, which can cause cardiac arrest, stroke, pulmonary edema, and other complications that can be fatal.